Economic evaluation of cognitive behavioural therapy for insomnia (CBT-I) for improving health outcomes in adult population: a systematic review protocol - Billingsley Kaambwa; Andrea Natalie Natsky; Andrew Vakulin; Ching Li Chai-Coetzer; Leon Lack; R. Doug McEvoy (BMJ Open)
Introduction Insomnia is associated with a number of adverse consequences that place a substantial economic burden on individuals and society. Cognitive behavioural therapy for insomnia (CBT-I) is a promising intervention that can improve outcomes in people who suffer from insomnia. However, evidence of its cost-effectiveness remains unclear. In this study, we will systematically review studies that report on economic evaluations of CBT-I and investigate the potential economic benefit of CBT-I as a treatment for insomnia.Methods and analysis The search will include studies that use full economic evaluation methods (ie, cost-effectiveness, cost-utility, cost-benefit, cost-consequences and cost-minimisation analysis) and those that apply partial economic evaluation approaches (ie, cost description, cost-outcome description and cost analysis). We will conduct a preliminary search in MEDLINE, Google Scholar, MedNar and ProQuest dissertation and theses to build the searching terms. A full search strategy using all identified keywords and index terms will then be undertaken in several databases including MEDLINE, Psychinfo, Proquest, Cochrane, Scopus, Cumulative Index of Nursing and Allied Health Literature (CINAHL), Web of Science and EMBASE. We will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for protocol guidelines in this review. Only articles in the English language and those reporting on adult populations will be included. We will use standardised data extraction tools for economic evaluations to retrieve and synthesise information from selected studies into themes and summarised in a Joanna Briggs Institute dominance ranking matrix.Ethics and dissemination No formal ethics approval will be required as we will not be collecting primary data. Review findings will be disseminated through a peer-reviewed publication, workshops, conference presentations and a media release.PROSPERO registration number CRD42019133554.